Β2-Adrenergic receptor agonists activate CFTR in intestinal organoids and subjects with cystic fibrosis. Issue 3 (28th July 2016) - Vijftigschild, Lodewijk A.W.; Berkers, Gitte; Dekkers, Johanna F.; Zomer-van Ommen, Domenique D.; Matthes, Elizabeth; Kruisselbrink, Evelien; Vonk, Annelotte; Hensen, Chantal E.; Heida-Michel, Sabine; Geerdink, Margot; Janssens, Hettie M.; van de Graaf, Eduard A.; et al.
We hypothesized that people with cystic fibrosis (CF) who express CFTR (cystic fibrosis transmembrane conductance regulator) gene mutations associated with residual function may benefit from G-protein coupled receptor (GPCR)-targeting drugs that can activate and enhance CFTR function. We used intestinal organoids to screen a GPCR-modulating compound library and identified β2 -adrenergic receptor agonists as the most potent inducers of CFTR function. β2 -Agonist-induced organoid swelling correlated with the CFTR genotype, and could be induced in homozygous CFTR-F508del organoids and highly differentiated primary CF airway epithelial cells after rescue of CFTR trafficking by small molecules. The in vivo response to treatment with an oral or inhaled β2 -agonist (salbutamol) in CF patients with residual CFTR function was evaluated in a pilot study. 10 subjects with a R117H or A455E mutation were included and showed changes in the nasal potential difference measurement after treatment with oral salbutamol, including a significant improvement of the baseline potential difference of the nasal mucosa (+6.35 mV, p<0.05), suggesting that this treatment might be effective in vivo . Furthermore, plasma that was collected after oral salbutamol treatment induced CFTR activation when administered ex vivo to organoids. This proof-of-concept study suggests that organoids can be used to identify drugs that activate CFTR function in vivo and to select route of administration. β2 -Adrenergic receptor agonists as CFTR activating drugs in subjects with CFTR residual function http://ow.ly/Dm44300wjuw